Strategi Guru Dalam Menanamkan Kecerdasan Spritual Anak Usia Dini di TK Dahlia Kecamatan Tabongo Barat - Nurhayati Tine; Yuliyana Bakari; Waode Eti Hardiyanti (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
Teachers' strategies in instilling spiritual intelligence in early childhood involve the application of a holistic and consistent approach. This study aimed to determine teachers' strategies in instilling spiritual intelligence in early childhood at Dahlia Kindergarten, Tabongo District, Gorontalo Regency. This study uses a descriptive qualitative method to describe teachers' strategies in instilling spiritual intelligence in early childhood. The subjects of the study were 2 educators consisting of 1 grade 1 teacher and the principal. Data collection techniques in this study were through observation, interviews and documentation. So it can be concluded that the teacher's strategy in instilling spiritual intelligence in children is by providing examples of good behavior first so that children can imitate it, teaching children to enjoy doing good and helping others, providing good understanding for children. and getting children used to diligently carrying out worship according to their religion, and providing motivation for children to achieve their dreams